Czy klauzula nadzwyczajnej zmiany stosunków ulegnie „nadzwyczajnej zmianie”? Neoinstytucjonalny paradygmat klauzuli rebus sic stantibus w obliczu multikryzysu - Wyszyński, Filip (PRAWO i WIĘŹ, 2026)
Recently, we have observed the phenomenon of multi-crisis, a multicausative crisis characterized by uncertainty and unpredictability in social life, including economic life. During this period of extraordinary volatility, the rebus sic stantibus clause is gaining importance. This multi-crisis forces a redefinition of the clause and a paradigm shift in its functionality. The aim of this study is to examine this clause in circumstances of extraordinary change. The premise of this research is to confront the clause within the framework of new institutional economics, which is becoming a research method in the economic analysis of law. This redefinition of the clause may occur against the backdrop of broader paradigm shifts and phenomena such as protectionism, deglobalization, and digitalization, and consequently, changes in the axiology of law. This study undertakes an analysis that goes beyond the standard dogmatic analysis of the legal institution of the rebus sic stantibus clause, but addresses the axiological and paradigmatic level within the legal system (the division of private law into civil and commercial law, the unification of law, the growing importance of soft law, and the privatization of public law). It seems that the rebus sic stantibus clause may acquire a broader axiological significance in the justice perspective.